2002
DOI: 10.2214/ajr.178.1.1780017
|View full text |Cite
|
Sign up to set email alerts
|

Using Contrast-Enhanced Helical CT to Visualize Arterial Extravasation After Blunt Abdominal Trauma

Abstract: Based on the limited reports of arterial extravasation in the nonhelical CT literature, the percentage (18%) of clinically stable patients in our study with CT scans showing arterial extravasation was higher than anticipated. This finding likely reflects the improved diagnostic capability of helical CT. Although the spleen and liver were the organs most commonly associated with arterial extravasation, radiologists should be aware that arterial extravasation may be associated with several other visceral injurie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(82 citation statements)
references
References 14 publications
0
80
0
2
Order By: Relevance
“…All of the reported traumatic CA dissections have been diagnosed by contrast-enhanced CT. CT has become the primary modality of radiologic evaluation for blunt trauma patients, and has been shown to be useful in detecting arterial injuries [12,13]. However, focal dissections of the CA can be missed by standard single-phase images with 5-mm thick sections [5], and we recommend repeat CT angiography or three-phase abdominal CT with 3-mm sections with reconstructed multiplanar images when injuries to visceral arteries are suspected and the initial CT is nondiagnostic.…”
Section: Discussionmentioning
confidence: 99%
“…All of the reported traumatic CA dissections have been diagnosed by contrast-enhanced CT. CT has become the primary modality of radiologic evaluation for blunt trauma patients, and has been shown to be useful in detecting arterial injuries [12,13]. However, focal dissections of the CA can be missed by standard single-phase images with 5-mm thick sections [5], and we recommend repeat CT angiography or three-phase abdominal CT with 3-mm sections with reconstructed multiplanar images when injuries to visceral arteries are suspected and the initial CT is nondiagnostic.…”
Section: Discussionmentioning
confidence: 99%
“…Further interventions, such as surgery or transcatheter arterial embolization, are usually indicated for haemostasis if extravasation is present with other unstable presentations (Fang et al, 2006;Yao et al, 2002). Transcatheter arterial embolization of a retroperitoneal haemorrhage caused by trauma or another specific cause is a well-documented and commonly used procedure (Velmahos et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…[13] A prospective multicenter trial using contrast-enhanced helical CT to evaluate stable patients found that 18.4% of patients with visceral injuries had arterial extravasation, and patients with arterial extravasation were significantly more likely to undergo TCE or surgery. [14] We preferred to use coils as embolic agent for the procedures in this study. The choice of embolic agent will vary based on the site and nature of the injury, the desire to preserve collateral flow, and operator experience.…”
Section: Discussionmentioning
confidence: 99%